For reasons of state : an exploder of received truths - Chomsky, Noam (New Delhi, 2003)
Back in print after thirty years, this is a classic collection of Chomsky essays. It is particularly valuable as the first of Chomsky's works to fully demonstrate his power as a political thinker. In his biting critiques of American foreign policy, the collection showcases his unique ability to join broader philosophical concerns with the political realities of his time.
Keywords: Civil disobedience